1970
DOI: 10.1172/jci106335
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis and lipogenesis from glucose in human fat cells of different sizes

Abstract: A B S T R A C T Lipogenesis from glucose and lipolysisin human omental and subcutaneous fat cells were studied as functions of adipose cell size and number in adult females. Since subcutaneous fat cells were larger than those prepared from the greater omentum, a comparison could be made of the metabolism of different sizes of cells within individual subjects. Rates per cell of glyceride-glycerol and glyceride-fatty acid synthesis from glucose were similar in omental and subcutaneous fat cells incubated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
1
2

Year Published

1972
1972
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(53 citation statements)
references
References 21 publications
5
45
1
2
Order By: Relevance
“…The finding of an increased rate of incorporation of glucose-U-"C into glyceride-glycerol in tissues containing large fat cells confirms previous reports on isolated epididymal fat cells from rats, guinea-pigs and hamsters (Girolamo and Mendlinger, 1969) and on isolated human subcutaneous fat eells (Goldrick and McLoughlin, 1970). Vinten and Gliemann (1970) obtained similar results with the incorporation of glucose-U-^^C into total glycerides in single rat epididymal fat cells of different sizes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding of an increased rate of incorporation of glucose-U-"C into glyceride-glycerol in tissues containing large fat cells confirms previous reports on isolated epididymal fat cells from rats, guinea-pigs and hamsters (Girolamo and Mendlinger, 1969) and on isolated human subcutaneous fat eells (Goldrick and McLoughlin, 1970). Vinten and Gliemann (1970) obtained similar results with the incorporation of glucose-U-^^C into total glycerides in single rat epididymal fat cells of different sizes.…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, the present findings are in agreement with previous studies on isolated fat cells (Goldrick and McLoughlin, 1970), but differ from the results obtained by Smith (1971) in human tissues and by Salans and Dougherty (1971) in rat epididymal fat cells. Whilst Smith's (1971) findings give rise to an entirely different interpretation, if the insulin effect is expressed not as a percentage increase above baseline but as an absolute increment, there is no satisfactory explanation for the discrepancy between our findings and those of Salans and Dougherty (1971).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hood and Allen (1978) also reported that the activities of the four NADPH-generating enzymes and the synthesis rate of fatty acids were directly related to adipose cell volume in four bovine intramuscular adipose samples. Similarly, in vitro experiments by Goldrick and McLoughlin (1970), Smith (1971b),…”
Section: Metabolic Traitsmentioning
confidence: 86%
“…On the other hand, basal lipolysis also increased in larger fat cells (Goldrick and McLoughlin, 1970) suggest ing an increased turnover rate of glyceride-glycerol in the enlarged fat cells. This may be one of the reasons for the increased rate of glucose incorporation into the larger cells (Smith, 1971b).…”
Section: Metabolic Traitsmentioning
confidence: 96%